Odpowiedź :
Odpowiedź:
x + 9 = 13 13 - 9 = 4
x = 4 4 + 9 = 13
x - 3 =8 8 + 3 = 11
x = 11 11 - 3 = 8
2x + 3 = 7 7 - 3 : 2 = 2
x = 2 2 * 2 + 3 = 7
12x = -36 -36 : 12 = -3
x = -3 12 * -3 = -36
liczę na naj ^^
x + 9 = 13
x = 13 - 9
x = 4
sprawdzenie:
4 + 9 = 13
13 = 13
zgadza się
x - 3 = 8
x = 8 + 3
x = 11
sprawdzenie:
11 - 3 = 8
8 = 8
zgadza się
2x + 3 = 7
2x = 7 -3
2x = 4 |:2
x = 2
sprawdzenie:
2*2 + 3 = 7
4 + 3 = 7
7 = 7
zgadza się
12x = -36 |:12
x = -3
sprawdzenie:
12*(-3) = -36
-36 = -36
zgadza się